From Agony to Enlightenment : parallelsbetween Rafael Lechowski's Quarcissusand T.S. Eliot's Four Quartets = De la agonía a la iluminación : paralelismos entre Quarcissus, de Rafael Lechowski, y Cuatro Cuartetos, de T.S. Elio - Saravia Vargas, Juan Carlos 1972-
Eliot's Four Quartetsstands as one of the most influential poetic works of the 20th Century. Therefore, academics have approached it from many different angles, among which one may mention its musicality, the references it contains, its composition, and the belief systems that converge in it, such as Christianity, Hinduism, and Buddhism. Rap music, on the other hand, is generally assumed to be a cultural product that lacks profound insights on the subjects it touches upon precisely because it is built for entertainment, not academic analysis. However, although rap music is generally regarded as non-academic, Rafael Lechowski's extensive rap work entitled Quarcissus: El arte de desamarhas divided criticism because of the way in which it engages with the subject of emotional pain. This article argues that Lechowski's work shares both structural and content features with Eliot's Four Quartets; particularlyregarding Buddhist principles, which is established by comparing the four sections that make up both texts.